DETERMINAN PENCEGAHAN FRAUD PADA BANK BUMN DI KOTA BATAM - Prima, Argo Putra; Janrosl, Viola Syukrina E.; Mulawarman, Mulawarman; Yusuf, Muhammad (JURNAL AKUNTANSI BARELANG, 2024)
This study aims to analyze the influence of internal audit and internal control on fraud prevention at state-owned banks in Batam City. It's critical to comprehend the elements that can stop fraud. Employees of state-owned banks in Batam were given questionnaires as part of the quantitative approach utilized in this study to collect data. The results of the study indicate that internal audit has a significant influence on fraud prevention. This indicates that the effectiveness of the internal audit function in identifying weaknesses and ensuring compliance with operational procedures plays an important role in minimizing the potential for fraud. However, the results of the study also show that internal control does not have a significant influence on fraud prevention partially. However, when tested simultaneously, internal audit and internal control together have a significant influence on fraud prevention. This finding emphasizes the importance of synergy between internal audit and internal control in creating an effective system to prevent fraud in the banking sector. Therefore, banks need to increase the role of internal audit and ensure good coordination with the internal control system to achieve optimal results in fraud prevention efforts.